Effect of salinity on the soybean plants symbiotic and photosynthetic apparatuses activity under rhizobia inoculation with the addition of Ge and Mo nanocarboxylates - Dmytro Kiriziy; Ivan Obeziuk; Lyudmyla Mykhalkiv; Sergii Kots (Біологічні студії)
Background. Soybean is one of the main oil and protein crops in the world, which occupies the largest cultivated area among legumes. However, adverse growing conditions, particularly salinity, can cause significant yield losses. It is known that salt stress affects morphological indices and physiological processes in soybean plants. Given the fact that the main factors contributing to the soybean-rhizobial symbiosis productivity are nitrogen fixation and CO2 assimilation, it is important to find ways to optimize these processes, in particular under salinity conditions. Materials and Methods. The research was conducted on symbiotic systems created with the participation of soybean plants (Glycine max (L.) Merr.) of the Samorodok variety and nodule bacteria Bradyrhizobium japonicum RS08 strain, cultivated with the addition of Ge and Mo nanocarboxylates. Results. It was revealed that salinity inhibited the activity of the symbiotic and photosynthetic apparatuses in soybean. With that, the degree of the symbiotic apparatus activity suppression under salinity conditions decreased over time. The addition of Ge nanocarboxylate to the inoculation suspension had a positive effect on the net CO2 assimilation rate in plant leaves under salinity at the bean-filling stage, and Mo – at all studied development stages. The transpiration rate closely correlated with the net assimilation rate, although the degree of its suppression by salinity was much less than that of photosynthesis. Positive correlations were found between nitrogen-fixing activity and the calculated net CO2 assimilation rate by the whole plant. A close positive correlation was found between the net assimilation rate at the bean filling stage and the grain productivity of soybean plants. At the same time, under inoculation with a suspension of rhizobia with the addition of Mo nanocarboxylate, the weight of the grain from the plant was the largest both among the control plants (without salinity) and among the salinity treatments. Conclusions. The obtained results indicate that, according to all investigated physiological parameters, inoculation of soybean seeds with Bradyrhizobium japonicum RS08 strain with the addition of Mo nanocarboxylate was the most effective in maintaining the activity of the symbiotic and photosynthetic apparatuses and, ultimately, grain productivity of plants both under normal conditions and under salinity.